Is Islam an enemy of the west? - Sonn, Tamara (Polity Press, 2016)
New York, Washington, Madrid, London and now Paris - the list of Western cities targeted by radical Islamic terrorists waging global jihad continues to grow. Tamara Sonn argues that whilst the West has many enemies among Muslims, it is politics not religion that informs their grievances. Islam, Sonn concludes, is not the problem, just as war is not the solution.